DIGITAL TRANSFORMATION OF CASH SERVICES: EMPOWERING WOMEN AND PROTECTING CHILDREN - Halid, Ilfanna; Rachman, Ellys; Katili, Andi Yusuf (Universitas Negeri Gorontalo, 2023)
This research aims to know ManagementFinanceRegional Treasury (Kasda) Online in the ServiceSocialEmpowermentWoman, ProtectionChild, Control Residents, and FamiliesPlanning for Bone Bolango Regency. The type of research used is descriptive using a qualitative approach method, which refers to 3 focus indicators, namely, Internet Network indicators, Implementing Capability, and Training. Research results show that: financial management on Regional Cash (Kasda) Online at the OfficeSocial, EmpowermentWoman, ProtectionChild, Population and Family Planning Control in Bone Bolango Regency is not yet optimal, this is due to poor internet networks, lack of thorough implementation, and lack of training related to financial management based on Regional Cash (Kasda) Online.